Perioperative renal calculus factors affecting percutaneous nephrolithotomy outcomes - Ketsuwan, Chinnakhet; Kongchareonsombat, Wisoot; Sangkum, Premsant; Kijvikai, Kittinut; Sananmuang, Thiparom; Leenanupunth, Charoen (Insight Urology, 2019)
Objective: Percutaneous nephrolithotomy has recently been the standard procedure for large kidney calculi. The aim of this study was to analyze the overall perioperative determinants of renal calculi that affect the results of percutaneous nephrolithotomy. Materials and Methods: In a single tertiary hospital in Bangkok, Thailand, Ramathibodi Hospital, we performed a retrospective analysis of patients who underwent percutaneous nephrolithotomy from 2011 to 2018. The character of the kidney stones was determined using computed tomography. A statistical analysis was performed to determine the associations between kidney stone factors and stone-free status after surgery: operative time (OT), estimated blood loss (EBL), renal function, hospital stay, and postoperative complications. Results: The comprehensive stone-free rate was 54.8%. Stone burden and stone density presented a statistically significant stone-free rate (p < 0.05). Only stone burden showed a correlation with postoperative blood loss and hospital stay. Conclusions: Stone burden and density of renal calculi are crucial parameters for the prediction of stone-free status.